Nogo-A regulates vascular network architecture in the postnatal brain. Issue 2 (February 2017) - Wälchli, Thomas; Ulmann-Schuler, Alexandra; Hintermüller, Christoph; Meyer, Eric; Stampanoni, Marco; Carmeliet, Peter; Emmert, Maximilian Y; Bozinov, Oliver; Regli, Luca; Schwab, Martin E; Vogel, Johannes; Hoerstrup, Simon P
Recently, we discovered a new role for the well-known axonal growth inhibitory molecule Nogo-A as a negative regulator of angiogenesis in the developing central nervous system. However, how Nogo-A affected the three-dimensional (3D) central nervous system (CNS) vascular network architecture remained unknown. Here, using vascular corrosion casting, hierarchical, synchrotron radiation μCT-based network imaging and computer-aided network analysis, we found that genetic ablation of Nogo-A significantly increased the three-dimensional vascular volume fraction in the postnatal day 10 (P10) mouse brain. More detailed analysis of the cerebral cortex revealed that this effect was mainly due to an increased number of capillaries and capillary branchpoints. Interestingly, other vascular parameters such as vessel diameter, -length, -tortuosity, and -volume were comparable between both genotypes for non-capillary vessels and capillaries. Taken together, our three-dimensional data showing more vessel segments and branchpoints at unchanged vessel morphology suggest that stimulated angiogenesis upon Nogo-A gene deletion results in the insertion of complete capillary micro-networks and not just single vessels into existing vascular networks. These findings significantly enhance our understanding of how angiogenesis, vascular remodeling, and three-dimensional vessel network architecture are regulated during central nervous system development. Nogo-A may therefore be a potential novel target for angiogenesis-dependent central nervous system pathologies such as brain tumors or stroke.